Peran Kontaminasi Kerak pada Diferensiasi Magma Pembentuk Batuan Vulkanik Sungai Ampalas, Mamuju, Sulawesi Barat - Draniswari, Windi Anarta; Kusuma, Sekar Indah Tri; Adimedha, Tyto Baskara; Sukadana, I Gde (EKSPLORIUM, 2020)
Anomalous radiometry has been found in Ampalas River Area on volcanic rock boulder. The values measured from gamma spectrometer are 787 ppm eU and 223 ppm eTh. This discovery is promising for exploration development. Further study need to figure the radioactive mineral bearing rock characteristic from in-situ samples. The research aim is to determine the petrology and geochemical characteristics of Ampalas volcanic rocks as preliminary study to find radioactive mineral accumulation process of Ampalas volcanic rocks. The methodologies are field observation, rock sampling, petrography, and X-Ray fluorescence (XRF) analyses. The Ampalas volcanic rocks consist of phonolite, phoidite, and phoid syenite. Their textures are porphyritic, flow, pyroxene rim, zoning, pseudo-leucite, corrosion, mafic inclusions, and sieve. The geochemical characteristics show high alkalinity and radioactive mineral enrichment disseminating on rock. The magmatic processes which play a significant role in radioactive mineral-bearing rocks formation are crystal fractionations (leucite and alkaline feldspar fractionations), continental crust assimilation, and magma mixing. Long interaction between magma and crust creates advanced magma differentiation causing higher uranium and thorium accumulation.